Developing accessible technologies for a changing world: understanding how people with vision impairment use smartphones. Issue 1 (2nd January 2022) - Locke, Kathryn; McRae, Leanne; Peaty, Gwyneth; Ellis, Katie; Kent, Mike
Abstract: Over a six week period, 845 people with low vision or blindness responded to our survey regarding how they used their smartphone, contributing to the first ever large-scale research project on the importance of smartphones in the Australian blind community. The results were significant − 79% of people with vision impairment use smartphones. They are part of their everyday lives and used for a broad range of purposes. Furthermore, the broad adoption of this device is a recent phenomenon – there has been a 365% increase in smartphone use in less than five years. While the rapid uptake of the smartphone by the vision impaired community demonstrates one level of 'access' is being achieved, we also identified ongoing issues impacting users. Our research demonstrates that people with disability must be included in the development process in order to ensure technological advancements are empowering and inclusive, especially in challenging times.